A study of a tensegrity structure for a footbridge - Pleşcan, C; Conţiu, M; Dósa, A (IOP Publishing, 2018)
It is known that tensegrity systems are made of isolated bars subjected only to compression, connected by stretched cables. The use of these structures comes with advantages such as making large openings and low consumption of materials. This paper analyses the problems related to the building and calculation of a 36-meter-long pedestrian bridge. The structure of the bridge is made up of a double arch of compressed bars and tensioned cables, which supports the path by means of cables. The structure has a number of kinematics degrees of freedom and is statically indeterminate in the same time, which means that it can be pretensioned. Pretensioning introduces compression efforts in the bars and tension efforts in the cables, which fixes the kinematic degrees of freedom and confers rigidity to the system, thus resulting a structure which can support the external loads. The paper deals with aspects of structural analysis and static calculation of the structure subjected to loads.